sncRNA-1 Is a Small Noncoding RNA Produced by Mycobacterium tuberculosis in Infected Cells That Positively Regulates Genes Coupled to Oleic Acid Biosynthesis - Coskun, Fatma S.; Srivastava, Shashikant; Raj, Prithvi; Dozmorov, Igor; Belkaya, Serkan; Mehra, Smriti; Golden, Nadia A.; Bucsan, Allison N.; Chapagain, Moti L.; Wakeland, Edward K.; Kaushal, Deepak; Gumbo, Tawanda; et al. (Frontiers in Microbiology, 2020)
Nearly one third of the world’s population is infected with Mycobacterium tuberculosis (Mtb). While much work has focused on the role of different Mtb encoded proteins in pathogenesis, recent studies have revealed that Mtb also transcribes many noncoding RNAs whose functions remain poorly characterized. We performed RNA sequencing and identified a subset of Mtb H37Rv-encoded small RNAs (<30 nts in length) that were produced in infected macrophages. Designated as smaller noncoding RNAs (sncRNAs), 3 of these predominated the read counts. Each of the three, sncRNA-1, sncRNA-6, and sncRNA-8 had surrounding sequences with predicted stable secondary RNA stem loops. Site-directed mutagenesis of the precursor sequences suggest the existence of a hairpin loop dependent RNA processing mechanism. A functional assessment of sncRNA-1 suggested that it positively regulated two mycobacterial transcripts involved in oleic acid biosynthesis. Complementary loss- and gain- of-function approaches revealed that sncRNA-1 positively supports Mtb growth and survival in nutrient-depleted cultures as well as in infected macrophages. Overall, the findings reveal that Mtb produces sncRNAs in infected cells, with sncRNA-1 modulating mycobacterial gene expression including genes coupled to oleic acid biogenesis.